2019
DOI: 10.1080/20477724.2019.1621729
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in the elderly: the role of age as a predictor of poor outcomes in hospitalized patients

Abstract: Background: The aim of this study was to investigate factors associated with poor outcomes among elderly hospitalized patients with leptospirosis. Methods: This is a retrospective cohort study with leptospirosis patients admitted to three tertiary hospitals in Fortaleza, Brazil, from January 1985 to July 2017. Patients were divided into two groups: elderly (age ≥60 years) and young (age <60 years). A comparison of demographical, clinical and laboratory data, treatment and outcomes was executed in order to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Daher et al have previously shown that age is a crucial predictor of outcomes. Elderly patients with leptospirosis showed less hemodynamic impairment on admission, higher incidence of AKI (OR 2.049, 95% CI 1.207–3.477), and a higher frequency of death (OR 3.520, 95% CI 1.940–6.386) during hospital stay than younger patients 13 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Daher et al have previously shown that age is a crucial predictor of outcomes. Elderly patients with leptospirosis showed less hemodynamic impairment on admission, higher incidence of AKI (OR 2.049, 95% CI 1.207–3.477), and a higher frequency of death (OR 3.520, 95% CI 1.940–6.386) during hospital stay than younger patients 13 .…”
Section: Discussionmentioning
confidence: 92%
“…In a prospective observational study, hemoglobin (Hb) levels lower than 11 g/dL were associated with severe forms of the disease (70% versus 14.8%; OR = 16.2 [95% CI 3.9-66.9]) 22 . Another study has shown that Elderly patients with leptospirosis showed less hemodynamic impairment on admission, higher incidence of AKI (OR 2.049, 95% CI 1.207-3.477), and a higher frequency of death (OR 3.520, 95% CI 1.940-6.386) during hospital stay than younger patients 13 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this bias alone does not seem sufficient to explain the age difference between our study and previous ones. Such a large proportion of patients age >60 should be of particular interest for clinicians: Older age has been associated with specific misleading clinical aspects: A possible lower incidence of myalgia, vomiting, and dyspnea has been suggested in a Brazilian study [ 11 ]; older age may increase the likelihood of hemodialysis requirement and worsen the prognosis of leptospirosis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on leptospirosis in the elderly have been performed in Brazil [ 11 , 17 ]. Watrin and colleagues reported that retired patients accounted for a third of leptospirosis cases diagnosed in Normandy (northwestern France) between 2010 and 2014 (unpublished study) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%